2021
DOI: 10.3389/fimmu.2021.771677
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Proteoglycan 4 Regulates Phagocytic Activation of Monocytes and Reduces IL-1β Secretion by Urate Crystal Stimulated Gout PBMCs

Abstract: ObjectivesTo compare phagocytic activities of monocytes in peripheral blood mononuclear cells (PBMCs) from acute gout patients and normal subjects, examine monosodium urate monohydrate (MSU) crystal-induced IL-1β secretion ± recombinant human proteoglycan 4 (rhPRG4) or interleukin-1 receptor antagonist (IL-1RA), and study the anti-inflammatory mechanism of rhPRG4 in MSU stimulated monocytes.MethodsAcute gout PBMCs were collected from patients in the Emergency Department and normal PBMCs were obtained from a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…THP-1 designates a spontaneously immortalized monocyte-like cell line, which has been widely used in studies of gout. Pam3CSK4 (50), PMA (51), LPS (52), and IL-6 (53) were all used for priming the THP-1 cells. Bone marrow derived monocytes (BMDM) are murine primary cells, for which priming is necessary as well.…”
Section: Discussionmentioning
confidence: 99%
“…THP-1 designates a spontaneously immortalized monocyte-like cell line, which has been widely used in studies of gout. Pam3CSK4 (50), PMA (51), LPS (52), and IL-6 (53) were all used for priming the THP-1 cells. Bone marrow derived monocytes (BMDM) are murine primary cells, for which priming is necessary as well.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a variety of studies reported that the maturation and release of IL-1β were related to the activation of the NLRP3 inflammasome, and activation of NLRP3 was an important pathway for MSU to contribute to inflammatory responses. Thus, we speculated whether the anti-inflammatory mechanism of neoastilbin was connected with the NLRP3 inflammasome [ 39 , 40 ]. In vitro and in vivo experiments showed that the expression of NLRP3, Caspase-1 and ASC proteins increased significantly after MSU stimulation, indicating that the NLRP3 inflammasome might be activated.…”
Section: Discussionmentioning
confidence: 99%
“…We employed the murine peritoneal model of acute gout as previously described ( Elsayed et al, 2021 ). Our experiments were approved by the IACUC committee at Chapman University.…”
Section: Methodsmentioning
confidence: 99%
“…Pyrogen-free MSU crystals (2 mg in 200 μL), vehicle (200 μL) or fingolimod (5 mg/kg; 200 μL) were administered intraperitoneally and peritoneal lavaging was performed at 4 h. Lavaging was performed by injecting 3 ml of cold DPBS into the peritoneal cavity followed by shaking for 30–60 s and lavage aspiration. Lavage fluids were centrifuged at 3,000 rpm for 5 min at 4°C, and cell pellets were resuspended in PBS and immunophenotyping of CMs, NCMs and neutrophils was conducted as previously described ( Elsayed et al, 2021 ). CMs were identified as CD11b+ Ly6C hi CCR2+, while NCMs were identified as CD11b+ Ly6C lo CD43 hi CX3CR1+ and neutrophils were identified as Ly6G + Ly6B.2+ ( Elsayed et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation